Students' Perceptions of Optional English Preparatory Program: A Case Study in a Turkish University - Ceyhun Yükselir (Literacy Trek, 2018)
Teachers' methods, students' perceptions in the prep-class and the literature review related show that determining language teaching methods and taking students' needs and perceptions into consideration in prep-classes could considerably affect the language learning process. Thus, this current study aims to examine the expectations of Turkish prep-class students who studied for one-year in optional prep-classes. A mixed methods convergent design was employed, using an adapted needs analysis questionnaire and unstructured interviews. The sample consisted of 110 graduate prep-class students from different departments in a state university. The results indicate that the majority of Turkish prep-class students think enrolling in the prep-class program is necessary; however, they lost their motivation for some reasons due to learning processes, systems or subjective factors. Besides, they expressed that materials were not suitable enough to improve their level of English and, in general, the prep-class program failed to meet their expectations in relation to program content and language learning processes. Regarding the four language skills, they expressed that productive skills should be given much more importance rather than receptive skills. In conclusion, instructors should try to motivate students more with the help of a variety of authentic materials and technological facilities and they should create an atmosphere in which productive skills are improved. Furthermore, the study suggests that the continuation of language learning processes should be ensured throughout the undergraduate program period, not just in the prep-class and makes some practical recommendations for researchers and educators.